The watchmaker's hand - Deaver, Jeffery (Deaver, Jeffery. Lincoln Rhyme novel, 2023)
"When a New York City construction crane mysteriously collapses, causing mass destruction and injury, Rhyme and Sachs are on the case. A political group claims responsibility for the sabotage and threatens another attack in twenty-four hours, unless its demands are met. The clock is ticking. Then a clue reveals to Rhyme that his nemesis, known as the Watchmaker, has come to town to fulfill his promise of murdering the criminalist. Now Rhyme and Sachs have to dodge his brilliant scheme to destroy them both, while racing against time to stop the construction site terrorists. With New York in a panic, Rhyme and his team must unravel a handful of plots as tightly wound as a timepiece--before more cranes fall, raining down death and destruction from above"--